Evaluasi Pendidikan Islam Dalam Pandangan Eksistensialisme - Dinar Pratama; Rijal, Syamsul; Silahuddin (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
Previous literature which focused on studying the philosophical basis of evaluating Islamic education was still not sufficient to provide a comprehensive understanding and tended to concentrate on Western thought. In fact, Islamic literature also has a strong basis to serve as a philosophical basis for evaluating Islamic education. This study aims to understand how the philosophy of existentialism can be used as a basis for thinking in the evaluation of Islamic education. The results of the study found that existentialism views students not as objects, but as dynamic subjects. In this case, the evaluation is not always carried out by the teacher to the students. However, students can also be encouraged to be able to do self-assessment. From the perspective of the Qur'an, the view of existentialism is also explained in the letter Ar-Rum verse 30 concerning human nature. This nature needs to be not passive but dynamic, so humans need to work on this nature so that it always develops into good things.